`root(6)((((x^-6)*(y^3))/((x^2)*(y^5)))^2)/(x/(y^-1))`

Simplify the expression.

### 1 Answer | Add Yours

`((x^(-6)y^3)/(x^2y^5))^2=(x^(-6-2)y^(3-5))^2`

`(x^(-8)y^(-2))^2=x^(-8xx2)y^(-2xx2)`

`=x^(-16)y^(-4)`

`root6(((x^(-6)y^3)/(x^2y^5))^2)=(x^(-16)y^(-4))^(1/6)`

`=x^(-16xx(1/6))y^(-4xx(1/6))`

`=x^(-8/3)y^(-2/3)`

`` `root6(((x^(-6)y^3)/(x^2y^5))^2)/(x/y^(-1))=(x^(-8/3)y^(-2/3))/(x/y^(-1))`

`=(x^(-8/3)y^(-2/3))/(xy)`

`=x^(-8/3-1)y^(-2/3-1)`

`=x^(-11/3)y^(-5/3)`

``

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes